2020
DOI: 10.1111/jph.12949
|View full text |Cite
|
Sign up to set email alerts
|

TaRPP13‐3, a CC‐NBS‐LRR‐like gene located on chr 7D, promotes disease resistance to wheat powdery mildew in Brock

Abstract: Disease resistance (R) gene, RPP13, plays an important role in the resistance of plants to pathogen infections; its function in resistance of wheat to powdery mildew remains unknown. In this study, a RNA‐Seq technique was used to monitor expression of genes in susceptible wheat ‘Jing411’ and resistant near‐isogenic line ‘BJ‐1’ in response to powdery mildew infection. Overall, 413 differential expression genes were observed and identified as involved in disease resistance. RPP13 homologous gene on wheat chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The R gene RPP13 encodes a protein containing a coiled-coil (CC) domain, nucleotide-binding site (NBS) and a leucine-rich repeat (LRR) region. This gene has been associated with resistance to downy mildew in A. thaliana (Bittner-Eddy and Beynon, 2001) and wheat (Liu et al, 2020b). Most of the intracellular R gene encoding NBS and LRR domain belong to a superfamily of genes that provide resistance to pathogens through point mutations that led to the recognition of specific effectors proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The R gene RPP13 encodes a protein containing a coiled-coil (CC) domain, nucleotide-binding site (NBS) and a leucine-rich repeat (LRR) region. This gene has been associated with resistance to downy mildew in A. thaliana (Bittner-Eddy and Beynon, 2001) and wheat (Liu et al, 2020b). Most of the intracellular R gene encoding NBS and LRR domain belong to a superfamily of genes that provide resistance to pathogens through point mutations that led to the recognition of specific effectors proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The homologues of the RPP13 gene identified in other plant studies were found to play a key role in resistance to fungi, bacteria and viruses. RPP13-like genes differ in the position and peptide length of the LRR domains and participate in resistance of tomato to yellow leaf curl virus [ 42 ], grape powdery mildew [ 43 ], sugarcane leaf shedding [ 44 ], wheat powdery mildew [ 45 ] and barley powdery mildew [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have, however, identified Rpp13-like NLR genes associated with powdery mildew resistance in cereals. In wheat, Liu et al 83 showed that silencing of the Rpp13 homologous gene TaRPP13-3 in resistant wheat cv. ‘Brock’ induced susceptibility to powdery mildew.…”
Section: Discussionmentioning
confidence: 99%